Improved Methods for Culturing the Subspecies of Oncomelania Hupensis: The Snail Hosts of Schistosoma Japonicum, the Oriental Human Blood Fluke - John Robert Putnam French (Hello World!, 1974)
For several decades, investigators have attempted to culture Oncomelania in various kinds of vivaria. However, they have failed to produce these snails in numbers sufficient to provide material for extensive research programs involving the S. japonicum cycle. Experimental studies of S. japonicum thus, have lagged far behind those of the other two widely distributed human schistosomes, S. mansoni and S. haematobium (Davis and Iwamoto, 1969).